Control of metal-support interaction in magnetic MoS2 catalyst to enhance hydrodesulfurization performance. Issue 5 (October 2021) - Zhu, Xiangyang; Bi, Qinling; Yang, Liangrong; Xing, Huifang; Wang, Li; Rong, Meng; Ni, Shan; Yuan, Menglei; Chen, Congmei; Liu, Huizhou
Abstract: Studies on the metal-support interaction have been a key step for deeply understanding the catalytic behavior of hydrodesulfurization (HDS) reactions. In particular, modification of the surface hydroxyl groups on alumina can determine its surface metal species and their dispersion degrees and thus influence the reactivity of catalysts. Herein, magnetic MoS2 nanoparticles supported on thiol groups grafted alumina (Fe3 O4 @Al2 O3 -SH@MoS2 ) were synthesized, leading to excellent catalytic hydrodesulfurization performance in a slurry-phase reactor of 40% desulfurization efficiency and high stability of 105 h in the long-term evaluation. Density functional theory calculations and multiple catalyst characterizations demonstrated that the grafting of thiol groups not only significantly weakened the metal-support interaction by bridging the support and active phase but also inhibited the coke formation, improved the cycle performance of the catalyst. This work proves to be an effective method to adjust the metal-support interaction, leading to enhanced catalytic performance. Besides, the magnetic properties of the catalyst enable it to be separated from the reaction media quickly, which is promising to be used in slurry reactors that process heavy crude oil. Graphical Abstract: In this work, we propose a novel strategy to regulate the metal-support interaction for enhanced hydrodesulfurization performance. ga1 Highlights: Magnetic Fe3 O4 @Al2 O3 -SH@MoS2 catalysts were carefully designed and synthesized. Metal-support interactions could be reduced by modification of Al2 O3 support with thiol groups. The catalyst exhibited excellent HDS performance and high stability in the actual diesel evaluation system. The thiol groups grafted on the alumina are conducive to the reduction of coke formation.